Prognosis and Predictors of Symptomatic Intracranial Hemorrhage After Endovascular Treatment of Large Vessel Occlusion Stroke - Huixin Shen; Qingfeng Ma; Liqun Jiao; Fei Chen; Sufang Xue; Jingya Li; Zhengping Li; Haiqing Song; Xiaoqin Huang (Frontiers in Neurology, 2022)
BackgroundSymptomatic intracranial hemorrhage (sICH) is a devastating complication of endovascular treatment (EVT) in patients with acute ischemic stroke (AIS) and is associated with high risk of disability and mortality. This study intended to evaluate the predictors of sICH after EVT in patients with large vessel occlusion (LVO)-induced AIS.MethodsWe conducted a retrospective review on consecutive AIS patients who underwent EVT in our University hospital between January 2019 and August 2020. The patients were classified into two groups based upon the occurrence of sICH. The main outcomes were the occurrence of sICH using the Heidelberg Bleeding Classification and functional condition at 90 days. Multivariate logistic regression analysis and receiver operating characteristics (ROC) curves were used to identify independent predictors of sICH after EVT.ResultsThree hundred and 69 patients were enrolled in the study, of which 16.8% (n = 62) developed sICH. Favorable neurological outcome was lower in patients with sICH than in patients without sICH (6.5 vs. 43.3%; P < 0.001), with the overall mortality being 112 (30.4%) at 90 days post- EVT. Results from univariate analysis showed significant differences between the two groups in the prevalence of diabetes, initial Alberta Stroke Program Early CT Score (ASPECTS) score, National Institutes of Health Stroke Scale (NIHSS) score after operation, the levels of fasting blood glucose (FBG), neutrophil to lymphocyte ratio (NLR), platelets (PLT), and thrombin time (TT) at admission. Multivariate logistic regression analysis showed that FBG ≥ 7.54 mmol/L (OR: 2.765; 95% confidence interval [CI]: 1.513–5.054), NLR ≥ 5.48 (OR: 2.711; 95% CI: 1.433–5.128), TT at admission ≥ 16.25 s (OR: 2.022; 95% CI: 1.115–3.667), and NIHSS score within 24 h after the operation ≥ 10 (OR: 3.728; 95% CI: 1.516–9.170) were independent predictors of sICH. The combination of NLR ≥ 5.48, FBG ≥ 7.54 mmol/L, TT at admission ≥ 16.25 s, and NIHSS score within 24 h after the operation ≥ 10 generated an optimal prediction model (AUC: 0.723).ConclusionHigher levels of FDG, NLR, TT at admission, and NIHSS score after operation were associated with sICH after EVT in patients with LVO-induced AIS.